2016
DOI: 10.4103/0972-2327.179976
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing nonadministration of thrombolytic therapy in early arrival strokes in a university hospital in Hyderabad, India

Abstract: Background:It is a well-known fact that very few patients of stroke arrive at the hospital within the window period of thrombolysis. Even among those who do, not all receive thrombolytic therapy.Objective:The objectives of this study were to determine the proportion of early arrival ischemic strokes (within 6 h of stroke onset) in our hospital and to evaluate the causes of nonadministration of intravenous and/or intraarterial thrombolysis in them.Materials and Methods:Data of all early arrival acute stroke pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…D-CT time in the current study was longer than three studies reported from India. [ 9 13 19 ] These were 17 (10–30) min, 31 ± 25.6 min, and 24 (10–47) min, respectively. The delay most commonly occurs when relatives are reluctant to make a decision about admitting and imaging the patient.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…D-CT time in the current study was longer than three studies reported from India. [ 9 13 19 ] These were 17 (10–30) min, 31 ± 25.6 min, and 24 (10–47) min, respectively. The delay most commonly occurs when relatives are reluctant to make a decision about admitting and imaging the patient.…”
Section: Discussionmentioning
confidence: 98%
“…Similar thrombolysis rate has been reported from a center in Hyderabad, India (89/2593, 3.4%). [ 13 ] From another center in Northwest India, the thrombolysis rate was 31.87% (189/593). However, the authors had calculated the percentage using eligible patients instead of all stroke patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Financial constraints were a big contributor, as has been observed in other studies in the country. 29 31 Thrombolytic agents are costly, particularly in private institutions. An Indian study reported 16% stroke patients who were eligible for TLT could not afford the therapy due to its high cost.…”
Section: Discussionmentioning
confidence: 99%